2014
DOI: 10.1136/bmjdrc-2014-000020
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of linagliptin in Hispanic/Latino patients with type 2 diabetes mellitus: a pooled analysis from six randomized placebo-controlled phase 3 trials

Abstract: ObjectiveThe number of individuals diagnosed with type 2 diabetes mellitus is expected to rise disproportionately in Hispanic/Latino populations. We therefore aimed to assess the efficacy and safety of the dipeptidyl peptidase-4 inhibitor linagliptin specifically in Hispanic/Latino patients with type 2 diabetes mellitus.Research design and methodsData from 745 patients who self-identified their ethnicity as Hispanic or Latino were pooled from six randomized, placebo-controlled phase 3 trials. Participants rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The glycemic efficacy and safety profile of sitagliptin in Hispanic patients observed in the analysis reported here are consistent with those previously reported for the entire populations of patients who participated in the studies which provided the data for this analysis and with those observed in the non-Hispanic cohort in the same trials. The results are also consistent with a similar analysis of Hispanic patients using data pooled from studies of linagliptin, another dipeptidyl-peptidase-4 inhibitor [ 24 ].…”
Section: Discussionsupporting
confidence: 87%
“…The glycemic efficacy and safety profile of sitagliptin in Hispanic patients observed in the analysis reported here are consistent with those previously reported for the entire populations of patients who participated in the studies which provided the data for this analysis and with those observed in the non-Hispanic cohort in the same trials. The results are also consistent with a similar analysis of Hispanic patients using data pooled from studies of linagliptin, another dipeptidyl-peptidase-4 inhibitor [ 24 ].…”
Section: Discussionsupporting
confidence: 87%
“…Low rates of AEs and incidence of hypoglycemia were observed in similar proportions in linagliptin and placebo-treated patients 56 . Long-term treatment of Japanese subjects with T2DM with linagliptin as monotherapy improved HbA 1c levels with no effect on body weight and few serious AEs 57 .…”
Section: Linagliptinmentioning
confidence: 71%
“…Furthermore, the efficacy of linagliptin was maintained irrespective of patients' renal function [27][28][29] , age 30 , race or ethnicity [31][32][33][34] , or duration of T2DM 35 .…”
Section: Linagliptinmentioning
confidence: 99%